Conflicts of interest in international organizations: evidence from two United Nations Humanitarian agencies - Mele, Valentina; Varone, Frederic; Anderfuhren-Biget, Simon (2016)
The independence of international civil servants (ICSs) from their country of origin is often presumed but rarely accounted for empirically. In order to address this gap, we investigate whether ICSs face conflicts between national and international interests and which conditions are more conducive to the manifestation of this conflict in international organizations. We adopt a mixed-methods design, including a survey with 1,400 respondents working in two United Nations humanitarian organizations, followed by semi-structured interviews with a purposive sample of respondents. The findings show that such conflicts matter for ICSs, hierarchical grade has stronger explanatory power than the other factors, and the higher the level in the international organization, the less frequently ICSs face conflict. The qualitative analysis explains these results by pointing to the effects of socialization among ICSs but also by shedding light on a related effect: dilution of national identity, as well as on the implications of locally recruiting lower-level staff.
Keywords: International organizations